Формування мережі об’єктів паркування індивідуального автотранспорту в історично сформованих містах (на прикладі м. Львова) - Любицький, Роман Ігорович (Національний університет "Львівська політехніка", 2018)
Дисертація присвячується виявленню теоретико-містобудівних передумов та підходів до формування мереж об’єктів паркування в історично сформованих містах (на прикладі м. Львова). В дисертації проаналізовано теоретичні та проектно-методичні підходи до розвитку мереж транспорту та об’єктів паркування. Розроблено комплексну методику дослідження мереж об’єктів паркування у історично сформованих містах. Виявлено особливості містобудівної організації мереж транспорту та об’єктів паркування в історично сформованих містах на прикладі Лейпцига та Кракова. Проаналізовано особливості формування та сучасну містобудівну організацію мереж транспорту та об’єктів паркування у м. Львів. Сформульовано теоретико-містобудівні підходи та концепції до вирішення проблеми та формування мережі об’єктів паркування в історично сформованих містах. The thesis is devoted to the revealing of theoretical town-planning preconditions and approaches to the formation of the parking facilities networks in historically developed cities (by the example of Lviv). Theoretical and project methodical approaches to the development of transport networks and parking facilities are analysed in the thesis. The principles of the development of cities in relation with the dominant type of urban transport are defined and analysed, the influence of motorization on the town-planning theories and conceptions is revealed. The role of private vehicle transport in modern theories of a sustainable development of cities, as well as strategies of parking management in historically developed cities are analysed. Taking into account the successful strategies of parking management and the standard and legal base of the European cities, the analysis of problems of the Ukrainian standard and legal base of parking is carried out. A complex methodology of investigation of parking facilities networks in historically developed cities is worked out, which is based on general scientific, architectural town-planning, specialized methods of investigation (including geoinformational analysis), as well as considers parking facilities networks in the context of adjacent scientific branches. The investigation of parking facilities networks as the structural elements of the transport networks of historically developed cities is divided in two stages: 1 – ‘investigation of the network of urban transport’; 2 – ‘investigation of the network and quality of parking facilities’. The aspects of town-planning organization of transport networks and parking facilities in historically developed cities by the example of Leipzig and Krakow are revealed. At the stage of the investigation of the network of urban transport, we performed: the analysis of the parameters of the functional and planning structure of cities, and revealed the development of IV ring roads, as well as tendencies towards functional decentralization, which eventually decreases the load of the streets-androads network; evaluation of urban mobility, with the help of which the prevalence of the mobility of public transport, pedestrian and biking travel over private vehicle transport was established. At the stage of the investigation of the network and quality of parking facilities, with the help of GIS-analysis, we have determined the level of provision of the citizens with parking, revealed the existence of parking lots “park and ride” and “park and walk”, the area of controlled parking, as well as a high level of parking management. Volume and space solutions of parking facilities are analysed. The aspects of the formation and the modern town-planning organization of transport network and parking facilities in the city of Lviv are analysed. The stages of the development of the planning structure and the network of urban transport of Lviv are generalised, the problems and the ideas for their solution are provided at each stage. At the stage of the investigation of the network of urban transport, we have performed: the analysis of the parameters of the functional and planning structure of cities and revealed the development of III ring roads, as well as the functional oversaturation of the municipal centre, which provokes the load of the streets-androads network; the evaluation of urban mobility with the help of which the prevalence of the mobility of private vehicle transport over alternative urban transport has been revealed. At the stage of the investigation of the network and quality of parking facilities, with the help of GIS-analysis, we have determined the level of provision of the citizens with parking, revealed the absence of parking lots “park and ride” and “park and walk”, an imperfect area of controlled parking as well as the low level of parking management. Theoretical town-planning approaches and conceptions have been formulated for the solution of the problem and the formation of the parking facilities network in historically developed cities. The preconditions for the formation of the optimal parking facilities network in historically developed cities have been provided, which include: 1 – optimization the streets-and-roads network; 2 – decentralization of the municipal historical centre of the city; 3 – extension of the network of public and bike transport and provision of its mobility; 4 – development of convenient and safe pedestrian communications; 5 – decrease of the vehicle presence in the historical part of the city. The model and approaches to the formation of the parking facilities network in historically developed cities have been formulated, which consist in zonation of the city by ‘parking priorities’, and condition the location of certain types of parking facilities in ‘central’, ‘medium’ and ‘peripheral’ areas. By the example of the city of Lviv, taking into account the peculiarities of the city and the high density of population, practical recommendations for the formation of the parking facilities network have been provided. Диссертация посвящена выявлению теоретико-градостроительных предпосылок и подходов к формированию сетей объектов парковки в исторически сложившихся городах (на примере г. Львова). В диссертации проанализированы теоретические и проектно-методические подходы к развитию сетей транспорта и объектов парковки. Разработана комплексная методика исследования сетей объектов парковки в исторически сложившихся городах. Выявлены особенности градостроительной организации сетей транспорта и объектов парковки в исторически сложившихся городах на примере Лейпцига и Кракова. Проанализированы особенности формирования и современную градостроительную организацию сетей транспорта и объектов парковки в г. Львов. Сформулированы теоретико-градостроительные подходы и концепции к решению проблемы и формирование сети объектов парковки в исторически сложившихся городах.
The formation of the parking facilities network of individual vehicle transport in historically developed cities (by the example of Lviv)
Формирование сети объектов парковки индивидуального автотранспорта в исторически сложившихся городах (на примере г. Львова)
Keywords: об’єкти паркування; історично сформоване місто; управління паркуванням; збалансований транспортний розвиток; parking facilities; historically developed city; parking management; sustainable transport development; объекты парковки; исторически сложившийся город; управление паркованием; сбалансированное транспортное развитие; 711.553.2(477.83-25)(043.5)